2019
DOI: 10.3389/fpls.2019.00194
|View full text |Cite
|
Sign up to set email alerts
|

Damage Kinetics at the Sub-micrometric Scale in Bast Fibers Using Finite Element Simulation and High-Resolution X-Ray Micro-Tomography

Abstract: This study combines experimental testing and computation analysis to reveal the role of defects and sub-micrometric microstructure in tensile behavior of hemp bast fibers. In particular, these structural defects represent the footprint of the processes to which the fibers elements are subject along the whole transformation chain from the plant to the end use product. Tensile experiments performed on elementary fibers and bundles in a wide diameter range (40–200 μm) are simultaneously conducted with X-ray micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A drawback of the study is that the fibre cross-section is assumed to be circular even though it is not, and the elasto-plastic constitutive law implemented for hemicellulose is better suited for metals. Further modelling developed by Guessasma et al [110] revealed that delaminated areas, weakly…”
Section: Including Defects In Mechanical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…A drawback of the study is that the fibre cross-section is assumed to be circular even though it is not, and the elasto-plastic constitutive law implemented for hemicellulose is better suited for metals. Further modelling developed by Guessasma et al [110] revealed that delaminated areas, weakly…”
Section: Including Defects In Mechanical Modellingmentioning
confidence: 99%
“…In the present review, we present a broader definition, dividing defects into two types: material discontinuity and the presence of inhomogeneity. Surface and bulk categories can further distinguish defects depending on their localization [110]. Surface discontinuities refer mainly to impurities or surface microcracks [111], whereas bulk discontinuities include cracks and interlaminar decohesion.…”
Section: Defects In the Plant Fibresmentioning
confidence: 99%
“…The mechanical properties of the cell walls are governed by several factors, such as the microfibrillar angle (Burgert and Keplinger 2013), the chemical composition (Lefeuvre et al 2014), the crystallinity, the defect density (Andersons et al 2009; Beaugrand and Guessasma 2015; Gourier et al 2017;Hughes 2012;Guessasma and Beaugrand 2019) and the mesoporosity (pore size between 2 and 50 nm), even if the last factor is not yet well established at the elementary fibre scale. Arnould et al (2017) mapped the stiffness of the cell wall of green flax stems by atomic force microscopy revealing a gradient in mechanical properties along the cross section at nanoscale.…”
Section: )mentioning
confidence: 99%
“…In addition, small internal cavities with diameters of a few µm were also reported as contributors to the porous structure of plant fibres [3][4][5]. This distinctive characteristic can be involved in the generation of stress concentrations, leading to the failure of the fibre [3,6,7]. Moreover, porosities in plant fibres are also the location of free water filling at high moisture content.…”
Section: Introductionmentioning
confidence: 99%